2023
DOI: 10.1371/journal.pone.0286091
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of an alkaline and detergent-stable Lipase from Fusarium annulatum Bugnicourt strain CBS associated with olive tree dieback

Abstract: This work describes a novel extracellular lipolytic carboxylester hydrolase named FAL, with lipase and phospholipase A1 (PLA1) activity, from a newly isolated filamentous fungus Ascomycota CBS strain, identified as Fusarium annulatum Bunigcourt. FAL was purified to about 62-fold using ammonium sulphate precipitation, Superdex® 200 Increase gel filtration and Q-Sepharose Fast Flow columns, with a total yield of 21%. The specific activity of FAL was found to be 3500 U/mg at pH 9 and 40°C and 5000 U/mg at pH 11 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Saraswat et al (2017) used a lipase enzyme for detergent formulation and found 15% increased wash efficiency from commercial detergent. Similarly, Dab et al (2023) reported a lipase from Fusarium annulatum which showed 50% increase in wash potential when applied in combination with commercial detergents. Li et al (2014) also reported a lipase from Pseudomonas stutzeri for detergent formulation with considerable increase in stain removal efficiency.…”
Section: Discussionmentioning
confidence: 97%
“…Saraswat et al (2017) used a lipase enzyme for detergent formulation and found 15% increased wash efficiency from commercial detergent. Similarly, Dab et al (2023) reported a lipase from Fusarium annulatum which showed 50% increase in wash potential when applied in combination with commercial detergents. Li et al (2014) also reported a lipase from Pseudomonas stutzeri for detergent formulation with considerable increase in stain removal efficiency.…”
Section: Discussionmentioning
confidence: 97%
“…20 Lipase enzymes break down greasy stains, and surfactants in detergents stick to the residue and remove stains from clothing. 21 Lipase is used along with other enzymes to remove the glue from the spools of yarn that aid in dyeing. 22 Lipases significantly increase oil yield during vegetable oil processing and improve the appearance of the final product.…”
Section: Introductionmentioning
confidence: 99%